Stimulation of Somatic Cell Reprogramming by ERas‐Akt‐FoxO1 Signaling Axis. (13th January 2014) - Yu, Yong; Liang, Dan; Tian, Qing; Chen, Xiaona; Jiang, Bo; Chou, Bin‐Kuan; Hu, Ping; Cheng, Linzhao; Gao, Ping; Li, Jinsong; Wang, Gang
ABSTRACT: Reprogramming of somatic cells to induced pluripotent stem cells (iPSCs) shares much similarity to the cancer initiation process, and the molecular mechanisms underlying both processes remain to be elucidated. Here, we report that a tumor‐ or embryonic stem cell‐specific Ras gene ERas, which encodes a constitutively active form of GTPase, and its downstream Phosphoinositide‐3 kinase/Akt signaling pathway are important facilitators for the somatic reprogramming process. We found that overexpression of ERas retrovirally enhanced mouse iPSC induction while ERas knockdown repressed it. Modulation of Akt signaling by genetic or chemical means greatly impacted the reprogramming efficiency. Forced expression of a constitutively active Akt1 gene could rescue the reduced efficiency resulting from ERas knockdown, and point‐mutation analyses further revealed that ERas is tightly coupled with Akt signaling to enhance reprogramming. Mechanistically, the forkhead transcription factor FoxO1 can function as a barrier to the iPSC induction, and the inactivation of FoxO1 by Akt‐dependent phosphorylation largely accounts for the enhancing effect of ERas‐Akt signaling on reprogramming. Collectively, these results unravel the significance of the ERas‐Akt‐FoxO1 signaling axis in iPSC generation, suggesting a possibly shared molecular basis for both somatic reprogramming and cancer initiation. Stem Cells   2014;32:349–363